The Relationship Between Early Initiation of Breastfeeding (EIBF) and Uterine Involution in Postpartum Mothers at PMB Irma Ahmad, Indrajaya District - Zaitun Zaitun; Salamah Salamah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Background The recovery process during the postpartum period is an important aspect for mothers after giving birth, considering the significant physiological and psychological changes. Physiological changes during the postpartum period include changes in the uterus, cervix, vulva and vagina, perineum, as well as the digestive system, urinary system, musculoskeletal system, endocrine system, vital signs, and hematological system. Changes in the uterus during the postpartum period, known as uterine involution, involve the process of returning the uterus to its pre-pregnancy size and shape. Uterine contractions are a crucial element in the uterine involution process; failure of contractions can result in uterine subinvolution or a slowing of the descent of the uterine fundus height (FHH). If subinvolution is not handled properly, this can cause ongoing bleeding to death (Harianto et al., 2018). The main cause of maternal death in Indonesia is bleeding, which reaches 30.3%. The normal uterine involution process can reduce the risk of bleeding, especially postpartum hemorrhage which is one of the direct causes of maternal death. Several factors that influence uterine involution include early maternal mobilization after delivery, breastfeeding, nutritional status, age, parity, postpartum exercise, psychological conditions, and early initiation of breastfeeding. (Maryunani, 2017). This study aims to determine the Relationship between Early Initiation of Breastfeeding (IMD) and Uterine Involution in Postpartum Mothers at PMB Irma Ahmad Indrajaya in 2024. This study is analytical with a Cross-sectional approach. The population in this study were all Postpartum Mothers at PMB Irma Ahmad, the study was conducted from November. Relationship between Early Initiation of Breastfeeding (IMD) and Uterine Involution in Postpartum Mothers at Irma Ahmad Midwifery Practice Indrajaya in 2024 with a ρ value of 0.003. It is hoped that midwives can provide IEC during pregnancy to postpartum and guidance to mothers in labor to increase knowledge about early initiation of breastfeeding because knowledge of early initiation of breastfeeding will increase the implementation of IMD practices Keywords: Early initiation of breastfeeding, Uterine involution